BIOMASA MANGROVE DAN BIOTA ASOSIASI DI KAWASAN PESISIR KOTA BONTANG - Yonvitner, Yonvitner; Wahyudin, Yudi; Mujio, Mujio; Trihandoyo, Arif (Perhimpunan Biologi Indonesia, 2019)
ABSTRACTMangrove is an important buffer ecosystem in the coastal area which has a function as carbon absorption through biomass growth. Others also as support any kind ecosystem particularly is fish's biodiversity. This research that was conducted in Bontang coast found 4 species of mangrove that dominated by Rhizophora apiculate that biomass production average 3714 kg/ha, Rhizophora mucronata 2415 kg/ha, Sonneratia 407 kg/ ha, and Bruguiera 251 kg/ha. Mangrove ecosystem support to biomass production of the shell, shrimp, mollusc until 2408 kg/ha of total population found. The research found that have a similar trend of mangrove growth and biomass related biota production. The message of this research is important of mangrove conservation to support biota and another ecosystem in the coastal area. Keywords: Mangrove, Association, Bontang,